MUTU ORGANOLEPTIK, KANDUNGAN PROTEIN DAN BETAKAROTEN MIE SUBSTITUSI IKAN RUCAH DAN UBI JALAR KUNING - Nuringtyas, Dyah Patria; Adi, Annis Catur (Media Gizi Indonesia, 2018)
Trash fish have a high protein content while the yellow sweet potato have a high betacarotene content that potential to be processed as noodle for supplementary feeding of toddlers age 2–5 years. This research aimed to analyze organoleptic and nutritional value (protein and betacarotene) of noodle trash fi sh and yellow sweet potato subtitution. Type of this research was true experimental design with completely randomized design with 5 times replication in 3 formulas which were 1 controlled formula (F0) and 2 modifi ed formulas (F1 and F2). Untrained panelists were used 25 mother of toddler. Data was analyzed descriptively and statistically to know the acceptence of noodle using Kruskal Wallis and Mann Whitney test (α=0.05). Kruskal Wallis statistical test indicated that there was significant difference (p<0.05) on the acceptability of aroma and texture of noodle and there was no significant difference (p>0.05) on the acceptability of colour and fl avour. The result of organoleptic test showed that the most preferred noodle by the panelis was formula F2 (37.5 g trash fi sh fl our and 37.5 g yellow sweet potato puree). Nutrient value of formula F2 had 12.28 g of protein and 208.8 mcg of betacaroten. The best composition, acceptability and nutritional value is F2 (37.5 g trash fish and 37.5 g yellow sweet potato puree) and can be used for alternative of supplementary feeding for toddler.